Solve for x:
4 lo g 2 x ( x ) + 2 lo g 4 x ( x 2 ) = 3 lo g 2 x ( x 3 )
This question is a part of the set Sooo many logs!!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good technique but please complete your solution for accuracy.
For those wondering how to actually solve the equation manually...
Start by using the exponent rule for logs so that we get just x inside each log:
2 1 ∗ 4 lo g 2 x ( x ) + 2 ∗ 2 lo g 4 x ( x ) = 3 ∗ 3 lo g 2 x ( x )
or,
2 lo g 2 x ( x ) + 4 lo g 4 x ( x ) = 9 lo g 2 x ( x )
Since all of the coefficients of x in the bases of each log are powers of 2, let's convert all of the logs to base 2 using the change of base formula:
lo g 2 ( 2 x ) 2 lo g 2 ( x ) + lo g 2 ( 4 x ) 4 lo g 2 ( x ) = lo g 2 ( 2 x ) 9 lo g 2 ( x )
Now we'll use the product and quotient rules for logs to simplify the denominators:
lo g 2 ( x ) − lo g 2 ( 2 ) 2 lo g 2 ( x ) + lo g 2 ( x ) + lo g 2 ( 4 ) 4 lo g 2 ( x ) = lo g 2 ( x ) + lo g 2 ( 2 ) 9 lo g 2 ( x )
which simplifies to:
lo g 2 ( x ) − 1 2 lo g 2 ( x ) + lo g 2 ( x ) + 2 4 lo g 2 ( x ) = lo g 2 ( x ) + 1 9 lo g 2 ( x )
Let y = lo g 2 ( x ) . Then by substitution, we have:
y − 1 2 y + y + 2 4 y = y + 1 9 y
Now let's get a common denominator on the left-hand side of the equation:
( y − 1 ) ( y + 2 ) 2 y ( y + 2 ) + ( y − 1 ) ( y + 2 ) 4 y ( y − 1 ) = y + 1 9 y
y 2 + y − 2 2 y 2 + 4 y + 4 y 2 − 4 y = y + 1 9 y
y 2 + y − 2 6 y 2 = y + 1 9 y
Cross-multiply and solve for y :
6 y 2 ( y + 1 ) = 9 y ( y 2 + y − 2 )
6 y 3 + 6 y 2 = 9 y 3 + 9 y 2 − 1 8 y
3 y 3 + 3 y 2 − 1 8 y = 0
3 y ( y 2 + y − 6 ) = 0
3 y ( y + 3 ) ( y − 2 ) = 0
This tells us that y can be 0, 2, or -3. Since y = lo g 2 ( x ) , we have x = 2 y , and then by substituting each value of y , we find that x can be either 1, 4, or 8 1 .
A standard technique taught for people taking multiple-choice tests is to quickly survey the possible answered and see how far you can get by eliminating impossible solutions. Often this is easier to do than plowing through a difficult math problem. As Avn noted earlier, this problem asks to solve for x and gives us several complicated terms involving x and three logarithms with a bases of x / 2 , 4 x , and 2 x respectively. The term involving the square root eliminates any solution suggesting a negative value of x . And since there is no definition for the logarithm function with a base of 0, any solution involving 0 is also eliminated. And that leaves only one possibility: 1 , 4 , 1 / 8 .
It is easy to see that 1 is a solution, since the logarithm of 1 is 0 for any base.
For 4 : we just verify that 4 lo g 2 2 + 2 lo g 1 6 1 6 = 3 lo g 8 6 4 ; i.e., 4 + 2 = 3 ∗ 2 .
For 1 / 8 : 4 lo g 1 / 1 6 2 − 3 / 2 + 2 lo g 1 / 2 ( 1 / 6 4 ) = 3 lo g 1 / 4 ( 1 / 5 1 2 ) , leads to 4 lo g 2 − 4 2 − 3 / 2 + 2 lo g 1 / 2 ( 1 / 6 4 ) = 3 lo g 2 − 2 ( 2 − 9 ) , which simplifies to ( 4 ∗ ( − 3 / 2 ) ) / ( − 4 ) + 2 ∗ 6 = 3 ∗ 9 / 2 , or 1 . 5 + 1 2 = 1 3 . 5 .
Here we use the general principle that lo g c x ( c y ) = y / x for any non-zero values of c , x , and y .
Problem Loading...
Note Loading...
Set Loading...
by observation since there is a root x in log therefore there can be no negative value for x and 0 cannot be a solution therefore the only options that remains is the first one :-)